Employee Involvement and Job Satisfaction: A Tale of the Millennial Generation (2018)
The purpose of this paper is to empirically study the effect of employee involvement in the workplace on job satisfaction for millennial workers in Colombia. Data were obtained from a sample of 2103 millennial employees working in 11 companies of different sectors located in the five main cities of Colombia. Ordered probit models were estimated to study the effect of employee involvement on job satisfaction, in general, and how different forms of participative decision-making in the workplace produce different impacts on individual satisfaction with objective and intrinsic aspects of the job, in particular. The empirical results show that, for millennial workers, there is a positive link between employee involvement and job satisfaction. Moreover, there is a higher positive impact on job satisfaction when millennial workers participate in decisions on general aspects of the company than when they participate in specific decisions such as those concerning teamwork or main tasks at work. Another interesting result is that millennial workers attach high importance to intrinsic aspects of their jobs (such as the possibility to use their knowledge in the work), which may improve their satisfaction in a higher participative environment.